Expression of toll-like receptors in porcine immune cells and tissues - Burkey, Thomas Edward. (Kansas State University, 2006)
Toll-like receptors (TLR) are instrumental in discriminating between pathogenic and commensal bacteria and act as mediators, along with downstream chemokines, of subsequent innate and adaptive immune responses. However, little is known about the expression and regulation of TLR or chemokines in swine. The objectives of the experiments described herein were to characterize the expression of porcine TLR and to identify regulatory patterns in these receptors in the presence of live Salmonella enterica serovar Typhimurium (ST) or Choleraesuis (SC). The first two experiments evaluated the in vivo and in vitro expression of TLR2, 4, 5 and 9. Our results indicate that TLR2, 4, 5 and 9 are constitutively expressed in vitro in a porcine jejunal epithelial cell line (IPEC-J2), porcine mononuclear phagocytes (pMPs) and in vivo in the distal ileum. In IPEC-J2 cells, ST elicited an increase in TLR2 mRNA (P < 0.05), and both ST and SC increased TLR2 mRNA in pMPs (P < 0.05). In vivo, oral challenge with ST increased (P < 0.05) both TLR2 and TLR4 mRNA in the distal ileum. In addition, the second experiment evaluated interleukin 8 (IL8) and CC chemokine ligand 20 (CCL20) expression in IPEC-J2 cells in response to ST or purified bacterial flagellin (Flag). TLR5 was constitutively expressed in the ileum and in IPEC-J2 and pMP cells. Interestingly, IL8 and CCL20 mRNA and protein were increased (P < 0.05) by ST and Flag, even in the absence of changes in TLR5. In the third experiment, the expression of TLR and chemoattractive mediators were evaluated in a panel of tissues obtained from pigs challenged with ST and SC. All genes of interest were constitutively expressed; however, the effects of treatment were limited to isolated tissues and genes. Taken together, the data indicate that TLR and chemoattractive mediators are expressed in porcine tissues and cells and that the observations described represent novel evidence that pig pathogens may regulate TLR expression and activate chemokine secretion.
Keywords: Porcine; Toll-like receptors; Salmonella; Agriculture, Animal Pathology (0476); Agriculture, General (0473); Biology, Animal Physiology (0433)